Comparison of different European and North American shoulder scoring systems - Alfahad, Nawaf (2018)
Background: Numerous shoulder scoring systems are in use world-wide to assess the outcomes from shoulder operations. Selecting the best outcome scoring instrument is challenging for the majority of musculoskeletal conditions. Outcome instruments can play an important role in the development of new procedures, techniques and protocols. The shoulder scoring systems that are currently used in North America are rarely applied alongside European shoulder scoring systems and vice versa. The lack of a universal shoulder scoring system impedes the evaluation process as it prevents valid comparison of outcomes from different research papers. The research aims were to develop a conversion equation for the six most commonly used outcome measures, to determine patients’ perceptions following shoulder arthroplasty surgery and to investigate differences between quantitative and qualitative outcomes in patients following shoulder arthroplasty surgery.